A Simple Model of An International Lender of Last Resort - Huang, Haizhou (IMF Working Papers; Working Paper ;, 2000)
This paper develops a simple model of an international lender of last resort (ILOLR). The world economy consists of many open economies, each with a banking system and a central bank operating under a pegged exchange rate regime. The fragility of the banking system and the limited ability of a domestic central bank to provide international liquidity together can cause currency and banking crises. An international interbank market can help an economy with the needed international liquidity, but with potential costs of international financial contagion. An ILOLR can play a useful role in providing international liquidity and reducing international contagion.